EVALUASI KEBIJAKAN TERHADAP PENGELOLAAN SAMPAH KAWASAN DAN TIMBULAN DI KOTA TANGERANG SELATAN - Muara Torang Hadomuan; Retnowati WD Tuti (Program Magister Ilmu Administrasi dan Kebijakan Publik, Pascasarjana, Universitas Pasundan, 2022)
The discussion in our study is about evaluating regional waste management policies and generation in South Tangerang City. In this policy, there are still many obstacles in the field, either performance or inadequate facilities. The achievement of policy objectives has not been optimal due to related parties to external factors, people who are less aware of waste management and the impact of waste hazards. This study aims to investigate the implementation of regional waste management and generation in South Tangerang City. The policy evaluation was analyzed from various aspects, namely: a) Effectiveness, policy evaluation is one of the important stages in the policy cycle. Policy evaluation is carried out after the public policy is implemented. This is to test the policies that have been made are successful or not. b) Efficiency, this is to show the best comparison between an activity and its results. This efficiency is a measure of success that is assessed in terms of human resources and costs to achieve the results of the policies implemented. c) Accuracy, to measure the extent to which a level of effectiveness satisfies a need, value, or opportunity to create a problem. d) Equity is a policy that is created and implemented which is oriented towards equity, meaning that it is a policy that is equitably distributed. e) Responsiveness, this criterion relates to how far a policy can satisfy the needs, preferences, or values ​​of certain groups. This criterion is very important because the analysis can satisfy other criteria. f) Accuracy, this criterion is closely related to rationality and substantive. Because the accuracy of the policy is not related to an individual criterion but two or more together. The method used in this study is a descriptive method with a qualitative approach. Waste management has been regulated, but its implementation has not run optimally. Waste management efforts in South Tangerang City are not enough just to rely on the establishment of Waste Banks and the involvement of the community to participate in managing and also sorting out biodegradable and non-biodegradable waste. In addition, the downstream waste problem will not be solved if the upstream does not implement the existing regulations. The government must conduct socialization to the community to sort organic and inorganic waste from home, sort waste from the generation and source areas, Temporary Disposal Sites (TPS) and Final Disposal Sites (TPA).